(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Glaucoma is considered to be the leading cause for blindness in patients. Intra-Ocular Pressure(IOP) is one of theprimary factors which plays an important role in the development of Glaucoma. There is a need for checking progression of Glaucoma in patients at early stage so thats progression can be controlled and/or necessary action can be taken. In this paper, we have surveyed various image processing techniques used for detection of Glaucoma in patients using various opthalmic tests.